Modelling bloom formation of the toxic dinoflagellates Dinophysis acuminata and Dinophysis caudata in a highly modified estuary, south eastern Australia. (20th December 2016) - Ajani, Penelope; Larsson, Michaela E.; Rubio, Ana; Bush, Stephen; Brett, Steve; Farrell, Hazel
Abstract: Dinoflagellates belonging to the toxigenic genus Dinophysis are increasing in abundance in the Hawkesbury River, south-eastern Australia. This study investigates a twelve year time series of abundance and physico-chemical data to model these blooms. Four species were reported over the sampling campaign - Dinophysis acuminata, Dinophysis caudata, Dinophysis fortii and Dinophysis tripos- with D. acuminata and D. caudata being most abundant. Highest abundance of D. acuminata occurred in the austral spring (max. abundance 4500 cells l −1 ), whilst highest D. caudata occurred in the summer to autumn (max. 12, 000 cells l −1 ). Generalised additive models revealed abundance of D. acuminata was significantly linked to season, thermal stratification and nutrients, whilst D. caudata was associated with nutrients, salinity and dissolved oxygen. The models' predictive capability was up to 60% for D. acuminata and 53% for D. caudata . Altering sampling strategies during blooms accompanied with in situ high resolution monitoring will further improve Dinophysis bloom prediction capability. Graphical abstract: